Do innate killing mechanisms activated by inflammasomes have a role in treating melanoma?. (20th February 2020) - Emran, Abdullah Al; Tseng, Hsin‐Yi; Coleman, Mikaela C.; Tiffen, Jessamy; Cook, Stuart; McGuire, Helen M.; Gallagher, Stuart; Feng, Carl; Hersey, Peter
Abstract: Melanoma, as for many other cancers, undergoes a selection process during progression that limits many innate and adaptive tumor control mechanisms. Immunotherapy with immune checkpoint blockade overcomes one of the escape mechanisms but if the tumor is not eliminated other escape mechanisms evolve that require new approaches for tumor control. Some of the innate mechanisms that have evolved against infections with microorganisms and viruses are proving to be active against cancer cells but require better understanding of how they are activated and what inhibitory mechanisms may need to be targeted. This is particularly so for inflammasomes which have evolved against many different organisms and which recruit a number of cytotoxic mechanisms that remain poorly understood. Equally important is understanding of where these mechanisms will fit into existing treatment strategies and whether existing strategies already involve the innate killing mechanisms.